Application quality function deployment (QFD) in small medium enterprise (SME) - Muhammad Muhibbudeen, Mohd Som (2008)
The aim for this study is to implement the Quality Function Deployment (QFD) in the Small Medium Enterprise (SME) to propose improvement on product development. The selected product was tapioca crips produce by Sukur Food Industry. As the project motivation, this study can help SME company to meet all the customer demand that can increase their product sales and profit. The QFD method begins with the survey application to gather the demands from customer. Then, the data collection is tranferred into House of Quality (HOQ) Matrix to analysis. The HOQ Matrix consists six stages, start from customer attribute, technical requirement, relationship matrix, roof of matrix, technical assessment and end at customer assessment stage. The packaging is the main modification that needs to consider as meeting the demand. This data supported by the result in customer assessment that show the company packaging is the lowest performance agains the competitor. So, the manufacturer has to change the packaging material and cooperate with appropriate organization to produce the quality packaging. This suggestion improvement hopefully could be used anywhere in the food industry and help the company to achieve their target.